Cost-Effective EdTech Paper 1: A position piece on how the sector can make progress - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech Horizon Scan: Rapid scan on emerging EdTech research during the Covid-19 pandemic. - Ampofo, Rudolph; Kaye, Tom (EdTech Hub, 2022)
EdTech Hub horizon scans are publications designed to provoke thinking and provide insight into a range of topics related to the design, implementation, oversight, and monitoring and evaluation of educational technology (EdTech) tools, products, services, and related ideas. This edition of the Hub’s Horizon Scan provides a high-level summary of research, blogs, and think-pieces published between October and December 2021, that provide insights and learnings on the adoption and utilisation of EdTech during the Covid-19 pandemic. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Cost-Effective EdTech Paper 2: Good practice - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Nudges to Improve Learning and Gender Parity: Preliminary findings on supporting parent-child educational engagement during Covid-19 using mobile phones - Aurino, Elisabetta; Tsinigo, Edward; Wolf, Sharon (EdTech Hub, 2022)
Key words: parental education engagement; caregiver engagement; nudges; text messages; schooling; learning; Ghana; gender In this study we evaluate a digital intervention to improve low-literate caregivers’ engagement with their children’s education and development in rural Ghana during the Covid-19 pandemic. The programme was a text-message-based behavioural change intervention for parents / caregivers that aimed to improve caregiver engagement in children’s educational activities, caregiver beliefs about returns to education, as well as children’s learning, enrollment, attendance, and gender parity in education. This household-randomised trial, conducted in the North East, Northern, Savannah, Upper East, and Upper West regions of Ghana, tested four variations of the intervention, varying both duration and a gender-parity focus. Households were randomised to one of five conditions: (i) regular behavioural nudges, 12 weeks; (ii) gender-boost behavioural nudges, 12 weeks; (iii) regular behavioural nudges, 24 weeks; (ii) gender-boost behavioural-nudges, 24 weeks; or (v) control. The interventions were implemented from January to April 2021 (for the 12-week groups) and January to June 2021 (for the 24-week groups). We collected data at midline (April–June 2021) and endline (August–September 2021). Our preliminary results suggest that a short, light-touch, SMS-based intervention can change caregiver behaviours and child outcomes in a rural, low-literate sample. However, the results were complex and intervention effectiveness depended on the caregiver having minimum levels of schooling. For caregivers with no education (65% of the sample), the intervention only increased caregiver expectations on reaching the desired level of education, especially among girls, but reduced educational engagement and some measures of children’s school enrollment and attendance. Educational engagement among Ghanaian caregivers is low relative to peer countries (Bornstein & Putnick, 2012; McCoy et al., 2018). The findings suggest that caregivers may need a base level of capital and resource (e.g., exposure to formal education) to enact the messages and increase their educational engagement with their children. Without this base level of capital, messages may increase caregivers’ aspirations for their children without providing enough support to change educational investments in positive ways. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 4: Content curation - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fourth of five reports on the development of a proof of concept for the Hub and describes our observations during content curation. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Should we paint all classroom roofs white to improve learning in Tanzania? - Proctor, Jamie (2022)
A growing literature base has developed from Global North contexts, showing a clear link between classroom temperature and student learning outcomes. However, very little evidence shows how this impact translates to low- and middle-income countries (LMICs), where average classroom temperatures are often high. The hypothesis for the research was that classroom temperatures in Tanzania are high and that a white-paint-cool-roof intervention would help mitigate these high temperatures. This study includes a literature review to understand the classroom policy in Tanzania, establish links between temperature and learning, and assess temperature retrofit options. Following this, the study presents the results of an experiment to trial a white-paint cool roof against a blue-paint roof and an unpainted control roof. Finally, data analysis predicts the intervention effects over an entire year and the subsequent impact on learning outcomes. The learning outcomes analysis includes a cost-effectiveness analysis using the Learning-Adjusted Years of Schooling (LAYS) metric. Empirical evidence of temperatures inside classrooms in Dar Es Salaam suggests that the temperature often exceeds 40℃. Literature searches indicate that this is the first time classroom air temperatures have been recorded and published for East Africa. The experiment involved using a low-cost retrofit intervention to reduce temperature – by painting the classroom roof blue or white over eight days. Results showed that the White Paint Intervention (WPI) reduced the temperature by around 3.7℃ over the course of the school day and up to a maximum of 5℃. The WPI was roughly twice as effective as the Blue Paint Intervention at reducing interior air temperatures. The WPI results were then modelled to estimate the classroom temperature reduction over a year, based on the assumed 3.5℃ reduction. Finally, using estimates from the existing literature, the learning impact of the intervention was calculated. The results suggest that using the WPI intervention can improve learning by 7.1%, which translates to an estimated 3.2 LAYS per classroom per year, at a cost-effectiveness of 5.3 LAYS per USD100. The paper shows that the impact of high temperatures in classrooms is likely undermining the funding currently channelled to improve learning outcomes in the region. Further, a WPI retrofit intervention is effective at reducing classroom temperatures in Tanzania. Due to climate-change-induced temperature increases, the intervention effectiveness is likely to increase over the coming decades. This paper was submitted as a dissertation in fulfilment of an MSc in Sustainability and Adaptation in the Built Environment at the Centre for Alternative Technology, Machynlleth, Powys (Wales)
Keywords: _r:AddedByZotZen

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen